Reduced graphene oxide coated iron phosphate composite material prepared based on waste graphite as well as preparation method and application of reduced graphene oxide coated iron phosphate composite material

By regenerating and utilizing graphite and lithium iron phosphate in waste lithium-ion batteries, reducing graphene oxide-coated iron phosphate composite materials are prepared, which solves the problem of waste lithium-ion batteries waste resources and low recycling efficiency, and realizes the recycling and utilization of high-performance positive electrode materials, reducing production costs.

CN119833616AActive Publication Date: 2025-04-15SOUTH CHINA UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510043896.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

In the prior art, waste and recycling efficiency of waste lithium-ion batteries is low, especially the recycling and utilization effect of the positive electrode material lithium iron phosphate and the negative electrode material graphite, which leads to waste of resources and environmental pollution.

Method used

By regenerating and ferric phosphate positive electrode materials of waste lithium iron phosphate batteries, a reduced graphene oxide coated iron phosphate composite material is prepared and applied to the positive electrode materials of lithium ion batteries to improve its electronic conductivity and lithium ion diffusion ability.

Benefits of technology

The cascade utilization of waste lithium-ion battery materials has been realized, the electrochemical performance and cycle stability of the cathode material have been improved, the production costs have been reduced, and it is in line with the concept of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833616A_ABST
    Figure CN119833616A_ABST
Patent Text Reader

Abstract

The invention discloses a reduced graphene oxide coated iron phosphate composite material prepared based on waste graphite as well as a preparation method and application of the reduced graphene oxide coated iron phosphate composite material. The method comprises the following steps: disassembling a waste lithium iron phosphate battery, and separating a positive electrode material waste lithium iron phosphate and a negative electrode material waste graphite; the method comprises the following steps: purifying waste graphite to obtain pure waste graphite; the preparation method comprises the following steps: preparing pure waste graphite into graphene oxide through a Hummers method; the method comprises the following steps: oxidizing waste lithium iron phosphate in the presence of an oxidizing agent to obtain iron phosphate; the preparation method comprises the following steps: mixing graphene oxide with iron phosphate, and carrying out hydrothermal reaction to obtain the reduced graphene oxide coated iron phosphate composite material. The reduced graphene oxide coated iron phosphate composite material prepared by the invention has excellent lithium storage performance and electrochemical stability, is suitable for a positive electrode material of a lithium ion battery, and effectively realizes resource utilization of waste lithium iron phosphate batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of resource utilization of new energy materials and environmental protection, and specifically relates to a reduced oxide graphene-coated iron phosphate composite material prepared based on waste graphite, and a preparation method and application thereof. Background Art

[0002] With the rapid development of new energy vehicles and large-scale energy storage markets, the demand for lithium-ion batteries is also growing rapidly. It is predicted that by 2030, the global total shipment of lithium-ion batteries will reach 5,000GWh. The service life of power batteries is generally 5-8 years. With the rapid development of lithium-ion batteries, their retirement volume is also expanding rapidly. In 2023, the weight of China's waste lithium-ion batteries exceeded 500,000 tons. How to properly dispose of these waste batteries has become an urgent problem to be solved. The main components of waste lithium-ion batteries include positive electrode materials, negative electrode materials, electrolytes, diaphragms, etc., among which positive and negative electrode materials are the most valuable resources. At present, the positive electrode material of power batteries is mainly lithium iron phosphate, and the negative electrode material is mainly graphite. If these resources rich in waste lithium-ion batteries are discarded at will, it will not only cause environmental pollution, but also a huge waste of resources. Therefore, it is of great significance to dismantle and recycle waste lithium-ion batteries and realize the reuse of electrode materials.

[0003] At present, the traditional recycling methods for lithium iron phosphate, the cathode material of waste lithium-ion batteries, mainly include pyrometallurgy and hydrometallurgy. Pyrometallurgy has high energy consumption and high pollution; hydrometallurgy has problems such as large consumption of chemical reagents such as acids and alkalis and serious environmental pollution. In addition, both methods recover precursor products such as transition metal salts or hydroxides, which need further processing before they can be re-applied to lithium-ion batteries, and the added value is not high. Direct regeneration technology is a mild green regeneration method that has emerged in recent years. It repairs the attenuated electrode material under relatively mild conditions by adding lithium sources, etc., so that its performance is restored. It can be directly used to manufacture new batteries, avoiding high energy consumption and the use of toxic chemicals, and has the advantages of green environmental protection and high added value. However, the existing direct regeneration technology is still not ideal for improving the conductivity of cathode materials.

[0004] As an important positive electrode material for lithium-ion batteries, lithium iron phosphate has the advantages of low cost, good thermal stability, and environmental friendliness, but its low electronic conductivity limits its further application. After long-term circulation, the structure of graphite negative electrode materials is often damaged to a certain extent, and it is difficult to guarantee the direct recycling and reuse performance. Therefore, how to efficiently extract iron phosphate and graphite from waste lithium iron phosphate batteries, reasonably modify them and prepare high-performance composite positive electrode materials is a key problem to be solved. On the other hand, there are relatively few studies on the recycling of graphite materials for negative electrodes of waste lithium-ion batteries. Graphite has excellent conductivity and can be used as a conductive filler to improve the conductivity of positive electrode materials. However, graphite is easy to agglomerate and has poor uniformity when mixed with positive electrode materials. Graphite can be prepared into graphene oxide with better conductivity after appropriate treatment. Therefore, it is of great significance to develop a method for preparing graphene oxide using recycled waste graphite as a raw material and uniformly coating regenerated positive electrode materials with it to improve the performance of positive electrode materials and realize the cascade utilization of waste lithium-ion battery materials. Summary of the invention

[0005] In order to solve the problems of waste resources and low recycling efficiency of waste lithium-ion batteries in the prior art, the present invention proposes a reduced graphene oxide-coated iron phosphate composite material prepared from waste graphite and its preparation method and application. The present invention recycles the graphite negative electrode and iron phosphate positive electrode materials of waste lithium iron phosphate batteries to prepare a reduced graphene oxide-coated iron phosphate composite material, and applies it to the positive electrode material of lithium-ion batteries, effectively improving its electronic conductivity and lithium ion diffusion capacity, thereby improving its electrochemical performance and cycle stability.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a reduced graphene oxide-coated iron phosphate composite material based on waste graphite, comprising the following steps:

[0008] (1) dismantling waste lithium iron phosphate batteries to separate waste lithium iron phosphate as the positive electrode material and waste graphite as the negative electrode material;

[0009] (2) Pretreatment of waste graphite: purifying the waste graphite obtained in step (1) to obtain pure waste graphite;

[0010] (3) preparing graphene oxide (GO): preparing graphene oxide from the pure waste graphite obtained in step (2) by the Hummers method;

[0011] (4) preparing iron phosphate (FePO4): oxidizing the waste lithium iron phosphate obtained in step (1) in the presence of an oxidant to obtain iron phosphate;

[0012] (5) Reduced graphene oxide coated with iron phosphate: The graphene oxide prepared in step (3) is mixed with the iron phosphate prepared in step (4), and subjected to a hydrothermal reaction to obtain a reduced graphene oxide coated with iron phosphate composite material.

[0013] Preferably, in step (2), the waste graphite is purified by etching with a NaOH solution.

[0014] Further preferably, the concentration of the NaOH solution is 0.01-0.04 M. Low-concentration NaOH solution can remove impurities on the graphite surface while causing less damage to the graphite.

[0015] More preferably, the etching treatment time is 2-10 hours.

[0016] Preferably, the specific steps of preparing graphene oxide by the Hummers method in step (3) include: mixing pure waste graphite with concentrated sulfuric acid, phosphoric acid and potassium permanganate in a mass ratio of (1-5): (120-700): (10-50): (6-30), reacting in an ice bath for 6-18 hours, then adding hydrogen peroxide for post-treatment to obtain a graphene oxide suspension, and then filtering, washing and drying to obtain graphene oxide. This method can efficiently oxidize graphite to GO, and the preparation process is simple and controllable.

[0017] More preferably, the mass concentration of concentrated sulfuric acid is above 95%; the mass concentration of phosphoric acid is above 80%;

[0018] Further preferably, the amount of hydrogen peroxide added is such that the color of the solution no longer changes.

[0019] Preferably, in step (4), the oxidant is at least one of hydrogen peroxide (H2O2), sodium persulfate (Na2S2O8) and potassium permanganate (KMnO4), and the molar ratio of waste lithium iron phosphate to the oxidant is (1-3): (1-2).

[0020] Preferably, the specific steps of preparing iron phosphate in step (4) are: adding waste lithium iron phosphate to an aqueous oxidant solution, stirring the reaction at 20-40° C. for 12-48 hours, and obtaining iron phosphate by filtering, washing and drying.

[0021] More preferably, the concentration of the aqueous oxidant solution is 0.05-0.2 mol / L.

[0022] Preferably, the temperature of the hydrothermal reaction in step (5) is 100-150° C., and the time of the hydrothermal reaction is 1-8 hours.

[0023] Preferably, in step (5), the mass ratio of graphene oxide to iron phosphate is (0.01-0.2):(1-2).

[0024] Further preferably, the mass ratio of graphene oxide to iron phosphate is (0.05-0.15):1.

[0025] Preferably, in step (5), graphene oxide and iron phosphate are dispersed in water for hydrothermal reaction, and the mass concentration of iron phosphate is 0.01-0.1 g / mL.

[0026] The reduced graphene oxide-coated iron phosphate composite material prepared by the above method.

[0027] The above-mentioned reduced graphene oxide-coated iron phosphate composite material is used as a positive electrode material for lithium-ion batteries.

[0028] The reduced graphene oxide coated FePO4 composite material prepared by the invention has excellent electrochemical performance and can be used as a positive electrode material for lithium ion batteries. The composite material not only improves the conductivity of FePO4, but also improves its cycle stability and rate performance.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] (1) The present invention uses graphite and lithium iron phosphate in waste lithium-ion batteries as raw materials, and prepares reduced graphene oxide-coated iron phosphate composite materials through simple chemical treatment and hydrothermal reaction, thereby realizing the recycling and reuse of battery materials and conforming to the concept of sustainable development.

[0031] (2) The present invention removes impurities from waste graphite through pretreatment, and the GO prepared by the Hummers method has high purity and excellent performance, providing a good carrier for the composite of FePO4.

[0032] (3) The present invention uses reduced graphene oxide to coat and modify iron phosphate to construct a conductive network, thereby improving the electronic conductivity of the material and buffering the volume change during the charge and discharge process, thereby improving the structural stability and cycle life of the material.

[0033] (4) The preparation method of the present invention is simple, has mild conditions, low production cost, and is easy to industrialize and apply, thus providing a new idea for the resource utilization of waste lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 XRD patterns of the reduced graphene oxide-coated iron phosphate (FePO4@rGO) obtained in step (4) of Examples 1, 7, and 8, the lithium iron phosphate powder (wLFP) obtained by disassembling step (3) of Example 1, and the FePO4 material obtained in Comparative Example 1.

[0035] Figure 2XPS graphs of reduced graphene oxide-coated iron phosphate (FePO4@rGO) obtained in step (4) of Examples 1, 7, and 8 and the FePO4 material obtained in Comparative Example 1.

[0036] Figure 3 SEM images of the reduced graphene oxide coated iron phosphate (FePO4@rGO) (bd) obtained in step (4) of Examples 1, 7 and 8, the FePO4 material (a) obtained in Comparative Example 1, and TEM images of the reduced graphene oxide coated iron phosphate (FePO4@rGO) (j, k, l) obtained in step (4) of Example 1, the graphene oxide powder (e, i) obtained in step (2) of Example 1, and the FePO4 powder (f, g, h) obtained in step (3) of Example 1.

[0037] Figure 4 The charge-discharge curves of the reduced graphene oxide-coated iron phosphate (FePO4@rGO) obtained in step (4) of Examples 1, 7, and 8 and the FePO4 material obtained in Comparative Example 1 at 0.1C.

[0038] Figure 5 The rate performance curves of the reduced graphene oxide-coated iron phosphate (FePO4@rGO) obtained in step (4) of Examples 1, 7, and 8 and the FePO4 material obtained in Comparative Example 1.

[0039] Figure 6 Cyclic performance curves of the reduced graphene oxide-coated iron phosphate (FePO4@rGO) obtained in step (4) of Examples 1, 7, and 8 and the FePO4 material obtained in Comparative Example 1 at 1C. DETAILED DESCRIPTION

[0040] The specific implementation of the present invention is further described below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. These embodiments are only used to illustrate the present invention and cannot limit the scope of the present invention in any way. Those skilled in the art can make various modifications under the teachings of the present invention, and these modifications are still within the protection scope of the present invention. It should be pointed out that if there are processes that are not particularly described in detail below, they are all realized or understood by those skilled in the art with reference to the prior art. If the manufacturer is not indicated for the reagents or instruments used, it is regarded as a conventional product that can be purchased commercially.

[0041] Example 1

[0042] A method for preparing reduced graphene oxide coated iron phosphate based on waste graphite, comprising the following steps:

[0043] (1) The graphite negative electrode sheet disassembled from the waste lithium iron phosphate battery was immersed and stirred in a 0.01M NaOH solution for 2 hours. After etching, the graphite was filtered out, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain pure waste graphite powder.

[0044] (2) Weigh 1g of the pure waste graphite powder obtained in step (1), slowly add it to a mixed acid solution consisting of 120mL of concentrated sulfuric acid (98wt%) and 13.3mL of phosphoric acid (85wt%), and stir evenly under an ice bath. Then slowly add 6g of potassium permanganate, control the temperature not to exceed 20°C and react for 6 hours. Add deionized water to the mixture for dilution, and then slowly add 10mL of 30wt% hydrogen peroxide until the color of the solution no longer changes. Filter, wash with 10% HCl solution and deionized water until neutral, and vacuum dry at 60°C for 12 hours to obtain brown-black graphene oxide (GO) powder.

[0045] (3) 5 g of lithium iron phosphate powder obtained from the positive electrode of waste lithium iron phosphate batteries was added to an aqueous solution containing 0.1 mol / L sodium persulfate (Na2S2O8) at a molar ratio of 2:1. The mixture was magnetically stirred at 30°C for 24 hours. After the reaction was completed, the mixture was filtered, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain black FePO4 powder.

[0046] (4) Take 0.1g of the graphene oxide obtained in step (2) and disperse it in 30mL of deionized water, and ultrasonicate it for 30 minutes to form a uniform dispersion. Add 1g of the FePO4 powder obtained in step (3) and continue ultrasonicating for 30 minutes. Transfer the mixture to a 50mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor and react at 120°C for 2 hours. After naturally cooling to room temperature, filter it, wash it with deionized water, and vacuum dry it at 60°C for 12 hours to obtain a reduced graphene oxide-coated iron phosphate (FePO4@rGO) composite material.

[0047] Example 2

[0048] A method for preparing reduced graphene oxide coated iron phosphate based on waste graphite, comprising the following steps:

[0049] (1) The graphite negative electrode sheet disassembled from the waste lithium iron phosphate battery was immersed and stirred in a 0.02M NaOH solution for 2 hours. After etching, the graphite was filtered out, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain pure waste graphite powder.

[0050] (2) Weigh 1g of the pure waste graphite powder obtained in step (1), slowly add it to a mixed acid solution consisting of 120mL of concentrated sulfuric acid (98wt%) and 13.3mL of phosphoric acid (85wt%), and stir evenly under an ice bath. Then slowly add 6g of potassium permanganate, control the temperature not to exceed 20°C and react for 6 hours. Add deionized water to the mixture for dilution, and then slowly add 10mL of 30wt% hydrogen peroxide until the color of the solution no longer changes. Filter, wash with 10% HCl solution and deionized water until neutral, and vacuum dry at 60°C for 12 hours to obtain brown-black graphene oxide (GO) powder.

[0051] (3) 5 g of lithium iron phosphate powder obtained from the positive electrode of waste lithium iron phosphate batteries was added to an aqueous solution containing 0.1 mol / L sodium persulfate (Na2S2O8) at a molar ratio of 2:1. The mixture was magnetically stirred at 30°C for 24 hours. After the reaction was completed, the mixture was filtered, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain black FePO4 powder.

[0052] (4) Take 0.1g of the graphene oxide obtained in step (2) and disperse it in 30mL of deionized water, and ultrasonicate it for 30 minutes to form a uniform dispersion. Add 1g of the FePO4 powder obtained in step (3) and continue ultrasonicating for 30 minutes. Transfer the mixture to a 50mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor and react at 120°C for 2 hours. After naturally cooling to room temperature, filter it with suction, wash it with deionized water, and vacuum dry it at 60°C for 12 hours to obtain a reduced graphene oxide-coated iron phosphate composite material.

[0053] Example 3

[0054] A method for preparing reduced graphene oxide coated iron phosphate based on waste graphite, comprising the following steps:

[0055] (1) The graphite negative electrode sheet disassembled from the waste lithium iron phosphate battery was immersed and stirred in a 0.03M NaOH solution for 2 hours. After etching, the graphite was filtered out, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain pure waste graphite powder.

[0056] (2) Weigh 1g of the pure waste graphite powder obtained in step (1), slowly add it to a mixed acid solution consisting of 120mL of concentrated sulfuric acid (98wt%) and 13.3mL of phosphoric acid (85wt%), and stir evenly under an ice bath. Then slowly add 6g of potassium permanganate, control the temperature not to exceed 20°C and react for 6 hours. Add deionized water to the mixture for dilution, and then slowly add 10mL of 30wt% hydrogen peroxide until the color of the solution no longer changes. Filter, wash with 10% HCl solution and deionized water until neutral, and vacuum dry at 60°C for 12 hours to obtain brown-black graphene oxide (GO) powder.

[0057] (3) 5 g of lithium iron phosphate powder obtained from the positive electrode of waste lithium iron phosphate batteries was added to an aqueous solution containing 0.1 mol / L sodium persulfate (Na2S2O8) at a molar ratio of 2:1. The mixture was magnetically stirred at 30°C for 24 hours. After the reaction was completed, the mixture was filtered, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain black FePO4 powder.

[0058] (4) Take 0.1g of the graphene oxide obtained in step (2) and disperse it in 30mL of deionized water, and ultrasonicate it for 30 minutes to form a uniform dispersion. Add 1g of the FePO4 powder obtained in step (3) and continue ultrasonicating for 30 minutes. Transfer the mixture to a 50mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor and react at 120°C for 2 hours. After naturally cooling to room temperature, filter it with suction, wash it with deionized water, and vacuum dry it at 60°C for 12 hours to obtain a reduced graphene oxide-coated iron phosphate composite material.

[0059] Example 4

[0060] A method for preparing reduced graphene oxide coated iron phosphate based on waste graphite, comprising the following steps:

[0061] (1) The graphite negative electrode sheet disassembled from the waste lithium iron phosphate battery was immersed and stirred in a 0.04M NaOH solution for 2 hours. After etching, the graphite was filtered out, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain pure waste graphite powder.

[0062] (2) Weigh 1g of the pure waste graphite powder obtained in step (1), slowly add it to a mixed acid solution consisting of 120mL of concentrated sulfuric acid (98wt%) and 13.3mL of phosphoric acid (85wt%), and stir evenly under an ice bath. Then slowly add 6g of potassium permanganate, control the temperature not to exceed 20°C and react for 6 hours. Add deionized water to the mixture for dilution, and then slowly add 10mL of 30wt% hydrogen peroxide until the color of the solution no longer changes. Filter, wash with 10% HCl solution and deionized water until neutral, and vacuum dry at 60°C for 12 hours to obtain brown-black graphene oxide (GO) powder.

[0063] (3) 5 g of lithium iron phosphate powder obtained from the positive electrode of waste lithium iron phosphate batteries was added to an aqueous solution containing 0.1 mol / L sodium persulfate (Na2S2O8) at a molar ratio of 2:1. The mixture was magnetically stirred at 30°C for 24 hours. After the reaction was completed, the mixture was filtered, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain black FePO4 powder.

[0064] (4) Take 0.1g of the graphene oxide obtained in step (2) and disperse it in 30mL of deionized water, and ultrasonicate it for 30 minutes to form a uniform dispersion. Add 1g of the FePO4 powder obtained in step (3) and continue ultrasonicating for 30 minutes. Transfer the mixture to a 50mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor and react at 120°C for 2 hours. After naturally cooling to room temperature, filter it with suction, wash it with deionized water, and vacuum dry it at 60°C for 12 hours to obtain a reduced graphene oxide-coated iron phosphate composite material.

[0065] Example 5

[0066] A method for preparing reduced graphene oxide coated iron phosphate based on waste graphite, comprising the following steps:

[0067] (1) The graphite negative electrode sheet disassembled from the waste lithium iron phosphate battery was immersed and stirred in a 0.01M NaOH solution for 2 hours. After etching, the graphite was filtered out, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain pure waste graphite powder.

[0068] (2) Weigh 1g of the pure waste graphite powder obtained in step (1), slowly add it to a mixed acid solution consisting of 120mL of concentrated sulfuric acid (98wt%) and 13.3mL of phosphoric acid (85wt%), and stir evenly under an ice bath. Then slowly add 6g of potassium permanganate, control the temperature not to exceed 20°C and react for 6 hours. Add deionized water to the mixture for dilution, and then slowly add 10mL of 30wt% hydrogen peroxide until the color of the solution no longer changes. Filter, wash with 10% HCl solution and deionized water until neutral, and vacuum dry at 60°C for 12 hours to obtain brown-black graphene oxide (GO) powder.

[0069] (3) 5 g of lithium iron phosphate powder obtained from the positive electrode of waste lithium iron phosphate batteries was added to an aqueous solution containing 0.08 mol / L sodium persulfate (Na2S2O8) at a molar ratio of 2:1. The mixture was magnetically stirred at 30°C for 24 hours. After the reaction was completed, the mixture was filtered, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain black FePO4 powder.

[0070] (4) Take 0.1g of the graphene oxide obtained in step (2) and disperse it in 30mL of deionized water, and ultrasonicate it for 30 minutes to form a uniform dispersion. Add 1g of the FePO4 powder obtained in step (3) and continue ultrasonicating for 30 minutes. Transfer the mixture to a 50mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor and react at 120°C for 2 hours. After naturally cooling to room temperature, filter it with suction, wash it with deionized water, and vacuum dry it at 60°C for 12 hours to obtain a reduced graphene oxide-coated iron phosphate composite material.

[0071] Example 6

[0072] A method for preparing reduced graphene oxide coated iron phosphate based on waste graphite, comprising the following steps:

[0073] (1) The graphite negative electrode sheet disassembled from the waste lithium iron phosphate battery was immersed and stirred in a 0.01M NaOH solution for 2 hours. After etching, the graphite was filtered out, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain pure waste graphite powder.

[0074] (2) Weigh 1g of the pure waste graphite powder obtained in step (1), slowly add it to a mixed acid solution consisting of 120mL of concentrated sulfuric acid (98wt%) and 13.3mL of phosphoric acid (85wt%), and stir evenly under an ice bath. Then slowly add 6g of potassium permanganate, control the temperature not to exceed 20°C and react for 6 hours. Add deionized water to the mixture for dilution, and then slowly add 10mL of 30wt% hydrogen peroxide until the color of the solution no longer changes. Filter, wash with 10% HCl solution and deionized water until neutral, and vacuum dry at 60°C for 12 hours to obtain brown-black graphene oxide (GO) powder.

[0075] (3) 5 g of lithium iron phosphate powder obtained from the positive electrode of waste lithium iron phosphate battery was added to an aqueous solution containing 0.12 mol / L sodium persulfate (Na2S2O8) at a molar ratio of 2:1. The mixture was magnetically stirred at 30°C for 24 hours. After the reaction was completed, the mixture was filtered, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain black FePO4 powder.

[0076] (4) Take 0.1g of the graphene oxide obtained in step (2) and disperse it in 30mL of deionized water, and ultrasonicate it for 30 minutes to form a uniform dispersion. Add 1g of the FePO4 powder obtained in step (3) and continue ultrasonicating for 30 minutes. Transfer the mixture to a 50mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor and react at 120°C for 2 hours. After naturally cooling to room temperature, filter it with suction, wash it with deionized water, and vacuum dry it at 60°C for 12 hours to obtain a reduced graphene oxide-coated iron phosphate composite material.

[0077] Example 7

[0078] A method for preparing reduced graphene oxide coated iron phosphate based on waste graphite, comprising the following steps:

[0079] (1) The graphite negative electrode sheet disassembled from the waste lithium iron phosphate battery was immersed and stirred in a 0.01M NaOH solution for 2 hours. After etching, the graphite was filtered out, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain pure waste graphite powder.

[0080] (2) Weigh 1g of the pure waste graphite powder obtained in step (1), slowly add it to a mixed acid solution consisting of 120mL of concentrated sulfuric acid (98wt%) and 13.3mL of phosphoric acid (85wt%), and stir evenly under an ice bath. Then slowly add 6g of potassium permanganate, control the temperature not to exceed 20°C and react for 6 hours. Add deionized water to the mixture for dilution, and then slowly add 10mL of 30wt% hydrogen peroxide until the color of the solution no longer changes. Filter, wash with 10% HCl solution and deionized water until neutral, and vacuum dry at 60°C for 12 hours to obtain brown-black graphene oxide (GO) powder.

[0081] (3) 5 g of lithium iron phosphate powder obtained from the positive electrode of waste lithium iron phosphate batteries was added to an aqueous solution containing 0.10 mol / L sodium persulfate (Na2S2O8) at a molar ratio of 2:1. The mixture was magnetically stirred at 30°C for 24 hours. After the reaction was completed, the mixture was filtered, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain black FePO4 powder.

[0082] (4) Take 0.05g of the graphene oxide obtained in step (2) and disperse it in 30mL of deionized water, and ultrasonicate it for 30 minutes to form a uniform dispersion. Add 1g of the FePO4 powder obtained in step (3) and continue ultrasonicating for 30 minutes. Transfer the mixture to a 50mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor and react at 120°C for 2 hours. After naturally cooling to room temperature, filter it with suction, wash it with deionized water, and vacuum dry it at 60°C for 12 hours to obtain a reduced graphene oxide-coated iron phosphate composite material.

[0083] Example 8

[0084] A method for preparing reduced graphene oxide coated iron phosphate based on waste graphite, comprising the following steps:

[0085] (1) The graphite negative electrode sheet disassembled from the waste lithium iron phosphate battery was immersed and stirred in a 0.01M NaOH solution for 2 hours. After etching, the graphite was filtered out, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain pure waste graphite powder.

[0086] (2) Weigh 1g of the pure waste graphite powder obtained in step (1), slowly add it to a mixed acid solution consisting of 120mL of concentrated sulfuric acid (98wt%) and 13.3mL of phosphoric acid (85wt%), and stir evenly under an ice bath. Then slowly add 6g of potassium permanganate, control the temperature not to exceed 20°C and react for 6 hours. Add deionized water to the mixture for dilution, and then slowly add 10mL of 30wt% hydrogen peroxide until the color of the solution no longer changes. Filter, wash with 10% HCl solution and deionized water until neutral, and vacuum dry at 60°C for 12 hours to obtain brown-black graphene oxide (GO) powder.

[0087] (3) 5 g of lithium iron phosphate powder obtained from the positive electrode of waste lithium iron phosphate batteries was added to an aqueous solution containing 0.10 mol / L sodium persulfate (Na2S2O8) at a molar ratio of 2:1. The mixture was magnetically stirred at 30°C for 24 hours. After the reaction was completed, the mixture was filtered, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain black FePO4 powder.

[0088] (4) Take 0.15g of the graphene oxide obtained in step (2) and disperse it in 30mL of deionized water, and ultrasonicate it for 30 minutes to form a uniform dispersion. Add 1g of the FePO4 powder obtained in step (3) and continue ultrasonicating for 30 minutes. Transfer the mixture to a 50mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor and react at 120°C for 2 hours. After naturally cooling to room temperature, filter it with suction, wash it with deionized water, and vacuum dry it at 60°C for 12 hours to obtain a reduced graphene oxide-coated iron phosphate composite material.

[0089] Example 9

[0090] A method for preparing reduced graphene oxide coated iron phosphate based on waste graphite, comprising the following steps:

[0091] (1) The graphite negative electrode sheet disassembled from the waste lithium iron phosphate battery was immersed and stirred in a 0.01M NaOH solution for 2 hours. After etching, the graphite was filtered out, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain pure waste graphite powder.

[0092] (2) Weigh 1g of the pure waste graphite powder obtained in step (1), slowly add it to a mixed acid solution consisting of 120mL of concentrated sulfuric acid (98wt%) and 13.3mL of phosphoric acid (85wt%), and stir evenly under an ice bath. Then slowly add 6g of potassium permanganate, control the temperature not to exceed 20°C and react for 6 hours. Add deionized water to the mixture for dilution, and then slowly add 10mL of 30wt% hydrogen peroxide until the color of the solution no longer changes. Filter, wash with 10% HCl solution and deionized water until neutral, and vacuum dry at 60°C for 12 hours to obtain brown-black graphene oxide (GO) powder.

[0093] (3) 5 g of lithium iron phosphate powder obtained from the positive electrode of waste lithium iron phosphate batteries was added to an aqueous solution containing 0.1 mol / L sodium persulfate (Na2S2O8) at a molar ratio of 2:1. The mixture was magnetically stirred at 30°C for 24 hours. After the reaction was completed, the mixture was filtered, washed with deionized water until neutral, and vacuum dried at 60°C for 12 hours to obtain black FePO4 powder.

[0094] (4) Take 0.1g of the graphene oxide obtained in step (2) and disperse it in 30mL of deionized water, and ultrasonicate it for 30 minutes to form a uniform dispersion. Add 1g of the FePO4 powder obtained in step (3) and continue ultrasonicating for 30 minutes. Transfer the mixture to a 50mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor and react at 100°C for 2 hours. After naturally cooling to room temperature, filter it with suction, wash it with deionized water, and vacuum dry it at 60°C for 12 hours to obtain a reduced graphene oxide-coated iron phosphate composite material.

[0095] Comparative Example 1

[0096] Without adding graphene oxide, the other conditions were the same as those in Example 1 to prepare uncoated regenerated FePO4 material.

[0097] Data Analysis:

[0098] Figure 1 XRD diagrams of reduced graphene oxide coated iron phosphate (FePO4@rGO) obtained in step (4) of Examples 1, 7, and 8, lithium iron phosphate powder (wLFP) obtained by disassembling step (3) of Example 1, and FePO4 material obtained in Comparative Example 1; it can be seen that the diffraction peaks in wLFP are highly consistent with the diffraction peaks of the PDF cards of LFP and FePO4, and LFP and FePO4 impurity phases are found in wLFP after cyclic retirement. Consistent with previous literature analysis, the main reason for the attenuation of LFP positive electrode materials is that the interface between LFP and FePO4 is constantly approaching from the surface to the bulk phase, thereby further hindering the Li + When FePO4 is coated with rGO at different concentrations, FePO4@rGO x The XRD patterns of (x = 0.05, 0.10 and 0.15) are consistent with the positions of the standard FePO4 diffraction peaks and are clearly visible. No other impurity peaks or C peaks are found, indicating that the reduction and coating process after the addition of GO does not change the crystal structure of FePO4. After oxidation by Na2S2O8, wLFP is completely converted into FePO4.

[0099] Figure 2 XPS graphs of the reduced graphene oxide-coated iron phosphate (FePO4@rGO) obtained in step (4) of Examples 1, 7 and 8 and the FePO4 material obtained in Comparative Example 1; it can be seen that all samples show typical C1s at ~284 eV, O1s at ~533 eV, F1s at ~686 eV, P 2p and P 2s at ~136 and 192 eV, respectively, and Fe 3p and Fe 2p at ~56 and 713 eV, respectively.

[0100] Figure 3The SEM images of the reduced graphene oxide coated iron phosphate (FePO4@rGO) (bd) obtained in steps (4) of Examples 1, 7, and 8, the FePO4 material (a) obtained in Comparative Example 1, and the reduced graphene oxide coated iron phosphate (FePO4@rGO) (j, k, l) obtained in step (4) of Example 1, the graphene oxide powder (e, i) obtained in step (2) of Example 1, and the TEM images of the FePO4 powder (f, g, h) obtained in step (3) of Example 1; from Figure 3 As can be seen from a in the figure, the FePO4 particles are spherical in shape, with uneven size distribution. The particle size is mainly distributed in the range of 100-500nm and the particle surface is smooth. Figure 3 As can be seen in b, the rGO reduced with 5wt% GO is not completely coated on the FePO4 particles, but the rGO is cross-linked and the FePO4 particles are not tightly bound to the rGO. However, from the rGO coated FePO4 particles ( Figure 3 c) in the figure shows that a thin layer of rGO is evenly coated on the FePO4 particles, and the size and shape of the coated FePO4 particles are clearly visible. When 15wt% GO is used to reduce the rGO-coated FePO4 particles ( Figure 3 In d), the surface of FePO4 particles is coated with thick rGO. TEM tests were performed to further observe the effects of graphene oxide and reduced graphene oxide coating on the morphology and structure of iron phosphate. Figure 3 As can be seen from the figure e, the Hummer method was used to successfully prepare graphene oxide with a wrinkled structure from waste graphite. By comparing FePO4( Figure 3 f) and FePO4@rGO 0.10 ( Figure 3 The TEM test results in Figure j) further prove that rGO is coated on the surface of FePO4 particles. It can be clearly observed that the (111) crystal plane of FePO4 with a lattice spacing of 0.342nm is tightly coated by an amorphous carbon layer with a thickness of about 5nm.

[0101] During the electrochemical performance test, 90wt% of active material (reduced graphene oxide coated iron phosphate (FePO4@rGO) obtained in step (4) of Examples 1, 7, and 8 and FePO4 material obtained in Comparative Example 1), 5wt% of acetylene carbon black, and 5wt% of poly(1,1 difluoroethylene) (PVDF) binder were mixed and ground to prepare a working electrode; N-methylpyrrolidone (NMP) solvent was used as a blending solvent. The resulting slurry was coated on a Cu box and then dried in a vacuum oven at 80°C for 24 hours. The prepared electrode was used as a working electrode, polypropylene (PP) as a diaphragm, 1M LiPF6 dissolved in ethylene carbonate / diethyl carbonate / ethyl methyl carbonate (volume ratio: 1 / 1 / 1) as an electrolyte, and a lithium metal sheet as a reference electrode were assembled into a 2032 button-type battery in a glove box under high-purity Ar. For subsequent electrochemical performance tests.

[0102] Figure 4 The charge-discharge curves of the reduced graphene oxide coated iron phosphate (FePO4@rGO) obtained in step (4) of Examples 1, 7, and 8 and the FePO4 material obtained in Comparative Example 1 at 0.1C; it can be seen that all samples exhibit a long stable platform at around 3.4V, which is a typical charge-discharge behavior of LiFePO4 positive electrode materials. The initial discharge capacity of FePO4 is 143.7mAh g -1 Compared with FePO4@rGO x The initial discharge specific capacities of (x=0.05, 0.10 and 0.15) are greatly improved, reaching 155.5, 166.8 and 152.7 mAh g, respectively. -1 At the same time, through Figure 4 The enlarged graph of the charge-discharge curve shows that after being coated with rGO at different concentrations, FePO4@rGO x The overpotentials of (x=0.05, 0.10 and 0.15) are also reduced to a certain extent. Compared with the other three materials (FePO4 is 126mV, FePO4@rGO 0.05 94mV and FePO4@rGO 0.15 90mV), FePO4@rGO 0.10 It exhibits a low overpotential of 77 mV. Figure 5 The rate performance curves of the reduced graphene oxide coated iron phosphate (FePO4@rGO) obtained in step (4) of Examples 1, 7, and 8 and the FePO4 material obtained in Comparative Example 1; it can be seen that at the rates of 0.1, 0.2, 0.5, 1, 2, 5, and 10C, the FePO4@rGO 0.10 The average reversible capacities are 166.8, 164.5, 159.6, 153.4, 145.8, 128.3, and 112.6 mAh g-1 It is worth noting that FePO4@rGO 0.15 The lower discharge capacity at 10C rate is mainly due to the thick rGO coating that hinders the Li + Rapid transport at high rates. When the rate is reduced from 10C to 0.1C, all FePO4@rGO x (x = 0.05, 0.10 and 0.15) and FePO4 all showed strong recovery, indicating the cyclic stability of the material structure.

[0103] Figure 6 The cycle performance curves of the reduced graphene oxide coated iron phosphate (FePO4@rGO) obtained in step (4) of Examples 1, 7, and 8 and the FePO4 material obtained in Comparative Example 1 at 1C; it can be seen that the other electrode (i.e., FePO4 is 125.6 mAh g -1 and 61.9%, FePO4@rGO 0.05 144.1 mAh g -1 and 63.2%, FePO4@rGO 0.15 143.9mAhg -1 and 86.7%), FePO4@rGO 0.10 It can provide a higher reversible initial specific capacity of 153.9 mAh g -1 The initial capacity retention rate after 500 cycles is 93.9% and the average CE after 500 cycles is 100%, which again shows that FePO4@rGO 0.10 The material has excellent cycle stability.

Claims

1. A method for preparing a reduced graphene oxide-coated iron phosphate composite material based on waste graphite, characterized in that: The following steps are involved: (1) dismantling waste lithium iron phosphate batteries to separate waste lithium iron phosphate as the positive electrode material and waste graphite as the negative electrode material; (2) Pretreatment of waste graphite: purifying the waste graphite obtained in step (1) to obtain pure waste graphite; (3) preparing graphene oxide: preparing graphene oxide from the pure waste graphite obtained in step (2) by the Hummers method; (4) preparing iron phosphate: oxidizing the waste lithium iron phosphate obtained in step (1) in the presence of an oxidant to obtain iron phosphate; (5) Reduced graphene oxide coated with iron phosphate: The graphene oxide prepared in step (3) is mixed with the iron phosphate prepared in step (4), and subjected to a hydrothermal reaction to obtain a reduced graphene oxide coated with iron phosphate composite material.

2. The method according to claim 1, characterized in that In step (2), the waste graphite is purified by etching with a NaOH solution, the concentration of the NaOH solution is 0.01-0.04M, and the etching time is 2-10h.

3. The method according to claim 1, characterized in that The specific steps of preparing graphene oxide by the Hummers method in step (3) include: mixing pure waste graphite with concentrated sulfuric acid, phosphoric acid and potassium permanganate in a mass ratio of (1-5): (120-700): (10-50): (6-30), reacting in an ice bath for 6-18 hours, then adding hydrogen peroxide for post-treatment, and then filtering, washing and drying to obtain graphene oxide.

4. The method according to claim 3, characterized in that: The mass concentration of concentrated sulfuric acid is above 95%; the mass concentration of phosphoric acid is above 80%; Add enough hydrogen peroxide until the solution no longer changes color.

5. The method according to claim 1, characterized in that In step (4), the oxidant is at least one of hydrogen peroxide, sodium persulfate and potassium permanganate, and the molar ratio of waste lithium iron phosphate to the oxidant is (1-3): (1-2).

6. The method according to claim 1, characterized in that The specific steps of preparing iron phosphate in step (4) are: adding waste lithium iron phosphate into an aqueous oxidant solution, stirring the reaction at 20-40° C. for 12-48 hours, and obtaining iron phosphate by filtering, washing and drying.

7. The method according to claim 1, characterized in that The temperature of the hydrothermal reaction in step (5) is 100-150° C., and the time of the hydrothermal reaction is 1-8 hours.

8. The method according to claim 1, characterized in that In step (5), the mass ratio of graphene oxide to iron phosphate is (0.01-0.2):(1-2).

9. A reduced graphene oxide-coated iron phosphate composite material obtained by the method according to any one of claims 1 to 8.

10. Use of the reduced graphene oxide-coated iron phosphate composite material according to claim 9 as a positive electrode material for a lithium ion battery.

Citation Information

Patent Citations

  • Method for preparing porous graphene by recycling graphite cathode materials from waste power batteries

    CN110589812A

  • Lithium supplementing and repairing method for waste lithium iron phosphate, and application thereof

    CN113072052A

  • Closed loop process for near zero-energy regeneration of electrodes by recycling spent rechargeable lithium batteries

    US20230207894A1

  • Methods and systems for producing dispersed graphene from spent lithium-ion batteries

    US20240076188A1